Identificação econométrica da relação entre choques de preços nos mercados de minério de ferro e de óleo combustível - Ramos, João Cardoso (2016)
This paper analyzes the relation between iron ore and bunker oil prices` returns for the period from June, 2008 to March, 2016. For this purpose, econometric models were estimated separately (through OLS technique) as well as jointly (through SURE approach) to capture contemporaneous correlations of the shocks of both prices. The result indicates the existence of a contemporaneously monthly correlation of about 20% between the shocks. Additionally, it indicates the absence of correlation and causality when prices are compared with lags. Therefore, one can assume that mining companies with revenues linked to iron ore prices and costs linked to bunker oil prices do partially benefit from natural hedge against shocks in those two markets.